Proceeding : 3rd International Qualitative Research Convention 2005, 21st - 23rd August 2005, Sofitel Palm Resort, Johor Bahru, Johor - International Qualitative Research Convention 2005 : Johor Bahru); Faculty of Education. University Teknologi Malaysia; Qualitative Research Association of Malaysia (Skudai : Universiti Teknologi Malaysia, 2005)
Proceeding of the third Internationl Qualitative Research Convention 2005 that managed by Faculty of Education, UTM
Keywords: Qualitative research -- Congresses; Research -- Methodology -- Congresses